Metodología de selección de refrigerantes alternativas ecológicas y eficientes energéticamente (2018)
To select a suitable refrigerant for a refrigeration or air conditioning system, certain thermodynamic variables must be taken into account, that need to be controlled together. To develop a methodology that integrates selection parameters that contemplate the requirements of the system, environmental protection, facilities and personnel security, in addition to energy efficiency, will make the process technically friendlier. The proposed methodology is framed in a multicriterio decision model of the parameters established by standards and norms that will allow the user - reader to define, in a simpler way, the refrigerant that provides the best benefits, also combining the requirements of the project with different substances, whose properties cover their needs efficiently. The findings show that natural refrigerants are an important alternative as refrigerant substances to replace synthetic refrigerants.